2018
DOI: 10.1098/rspb.2017.2617
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of thermal tolerance and its relationship with growth rate in juvenile mussels (Mytilus californianus)

Abstract: Complex life cycles characterized by uncertainty at transitions between larval/juvenile and adult environments could favour irreversible physiological plasticity at such transitions. To assess whether thermal tolerance of intertidal mussels () adjusts to post-settlement environmental conditions, we collected juveniles from their thermally buffered microhabitat from high- and low-shore locations at cool (wave-exposed) and warm (wave-protected) sites. Juveniles were transplanted to unsheltered cages at the two l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…Due to their sessile nature, which limits behavioral thermoregulation, intertidal mussels experience large body temperature fluctuations with each tidal cycle (Dowd et al, 2015;Jimenez et al, 2015;Miller and Dowd, 2017). Mussels living at different heights on the shore, and with different wave exposures, experience different daily temperature ranges, which allows one to study members of the same species that live in close proximity, but which have substantially different thermal histories (Denny et al, 2011;Gleason et al, 2018;Jimenez et al, 2015;Miller and Dowd, 2017;Moyen et al, 2019;Zippay and Helmuth, 2012). Furthermore, on many rocky shores, mussels are the dominant competitor for space in the mid-intertidal zone, and therefore play an important role in intertidal community ecology (Bayne et al, 1976;Gaylord et al, 2011;Mislan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to their sessile nature, which limits behavioral thermoregulation, intertidal mussels experience large body temperature fluctuations with each tidal cycle (Dowd et al, 2015;Jimenez et al, 2015;Miller and Dowd, 2017). Mussels living at different heights on the shore, and with different wave exposures, experience different daily temperature ranges, which allows one to study members of the same species that live in close proximity, but which have substantially different thermal histories (Denny et al, 2011;Gleason et al, 2018;Jimenez et al, 2015;Miller and Dowd, 2017;Moyen et al, 2019;Zippay and Helmuth, 2012). Furthermore, on many rocky shores, mussels are the dominant competitor for space in the mid-intertidal zone, and therefore play an important role in intertidal community ecology (Bayne et al, 1976;Gaylord et al, 2011;Mislan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Yet we are aware of only one study that has evaluated the effects of removing this variability. Gleason et al (2018) found that the thermal performance of both high-and low-zone juvenile mussels' (as assessed by the temperature at which 50% of mussels died, LT 50 ) decreased after 28 days of constant submersion, while the LT 50 of adult mussels did not change (Gleason et al, 2018). Research on other organisms suggests that adult mussels with different thermal histories might respond differently to constant submersion (Burggren, 2018;Jimenez et al, 2015;Wang et al, 2019;Williams and Somero, 1996) an avenue that Gleason et al (2018) explored only in juvenile, but not adult, mussels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We compared mussels living at high and low intertidal heights to determine whether heating rate differentially affected cardiac thermal tolerance in animals acclimatized to different exposure conditions. We hypothesized that, because high-zone mussels have a higher cardiac thermal tolerance and experience faster mean daily heating rates than low-zone mussels (Compton et al, 2018;Gleason et al, 2018;Miller and Dowd, 2017), high-zone mussels would better tolerate faster heating rates.…”
Section: Introductionmentioning
confidence: 99%
“…temperature, pH, dissolved oxygen, or salinity) during the experiments. Under all treatments, mussels were fed a commercial shellfish diet (Shellfish Diet 1800, Reed Mariculture, Campbell, CA, USA) three to four times per week according to the manufacturer's instructions [31].…”
Section: Methodsmentioning
confidence: 99%